Ginkgo ketone ester tablets for the treatment of cognitive impairment associated with chemotherapy for breast cancer - a prospective cohort study - Jiajing Chen; Lixin Chen; Kexin Jiang; Dandan Wang; Chunyu Wu; Yuenong Qin; Sheng Liu (Frontiers in Pharmacology)
BackgroundChemotherapy-related cognitive impairment (CRCI) affects up to 75% of breast cancer patients during treatment, with 35% experiencing persistent post-treatment deficits. Current interventions show limited efficacy, creating urgent need for targeted therapies. Ginkgo Ketone Ester (GBE), containing neuroprotective flavonoids and terpene lactones, represents a potential therapeutic strategy.MethodsThis 24-week prospective cohort study enrolled 96 breast cancer patients (stage I-III) receiving anthracycline-based chemotherapy. Participants were allocated to GBE intervention (n = 48) or standard care (n = 48) groups. The GBE cohort received tablets containing 14.08–21.12 mg total flavonoids, ≥9.6 mg flavonol glycosides, and ≥2.4 mg terpene lactones (0.25 g, three times daily) for 12 weeks. Cognitive function was assessed using Memory and Executive Screening (MES), Auditory Verbal Learning Test-Huashan Version (AVLT-H), and Shape Trail Test A/B at baseline, week 12, and week 24. Serum biomarkers (glutathione [GSH], reactive oxygen species [ROS], tumor necrosis factor-alpha [TNF-α]) and quality of life measures were evaluated correspondingly.ResultsGBE administration significantly improved cognitive performance compared to controls (P < 0.05). The intervention group demonstrated 23% higher MES scores (72.29 ± 9.09 vs. 64.42 ± 8.63 at week 24), 31% better AVLT-H performance, and maintained stable completion times. Biochemical analysis revealed substantial GSH elevation (56% increase) and ROS reduction (41% decrease) at week 24, while TNF-α remained unchanged. CRCI incidence was significantly lower in the GBE group (66.67% vs. 89.58%, P < 0.007). Treatment compliance reached 89% with no serious adverse events reported.ConclusionGBE demonstrates significant promise as a neuroprotective intervention for CRCI management, with substantial improvements in cognitive function and oxidative stress biomarkers. The favorable efficacy profile, excellent safety record, and high compliance support GBE’s potential as adjunctive CRCI therapy. While neuroinflammatory effects were limited, robust antioxidant restoration and cognitive enhancement warrant further investigation through large-scale randomized controlled trials to validate long-term efficacy and optimize clinical protocols.Clinical Trial Registrationhttps://www.chictr.org.cn, identifier ChiCTR2200065694.